Delamination mechanism study of large size waste printed circuit boards by using dimethylacetamide - Verma H.R.; Singh K.K.; Mankhand T.R. (My University, 2025)
Present work investigates the recycling of waste printed circuit boards (PCBs) by cracking of its multi-layered structure by using dimethylacetamide (DMA). The study shows that cracking and separation of layers of PCBs increases as the temperature increases; and decreases as the surface area of PCBs increases. After separation of layers, the used solvent was analyzed by proton and carbon nuclear magnetic resonance spectroscopy (NMR) to understand the dissolution phenomenon of resin. Further, NMR and Fourier transform infrared spectroscopy analysis of DMA sample after 1 h, 2 h, 3 h, 4 h and 8 h of reaction with PCBs at 433 K and PCB:DMA ratio (wt/vol) of 3:10 has been carried out to investigate the mechanism of dissolution of resin. These studies revealed that hydroxyl group of PCBs polymeric chain participates in hydrogen bonding with parent carbonyl group of DMA molecule that results in the solvation of resin. Possible chemical reaction based on the above finding has been discussed. Using this technique, separation of the metallic fraction without application of any energy intensive mechanical pre-processing is possible. © 2017 Elsevier Ltd